Educa????o pelo tempo do r??dio: desafios e perspectivas - Albertin, Daniela Oliveira (2016)
This research aims to rescuerecover Brazilian radio's memory and discuss its importance while educational proposal in the public schools of S??o Paulo. It is a study that reviews essentially, Paulo Freire's postulates regarding the pedagogy while liberating practice; discusses some concepts of Michel Foucault on power and domination structures that imprison models placed in various fields of society; and systematize the most central questions about the school projects within the public school, prioritizing his practical perspective from educommunication of Ismar de Oliveira Soares??? theoretical reference. In a more general understanding, starting the premise that the school is not the only owner of "knowledge", daily, we encounter with many "places" where the subject apprehend the most diverse types of knowledge, information and culture. The medias stands out between these spaces of knowledge and experience as a means of interaction very close to our daily lives. This approximation, given the mobility and fluidity of the current society, happens in a faster way. It is known that the media insert concepts, produce images suggest ideologies, creating a the medium itself to act on all of us. The approximation between the education and communication as epistemological fields of a possible dialogue, allows new teaching practices can be identified, analyzed and expanded, in view of the current social context and its urgencies. In this sense, it is necessary a review not only of the traditional curriculum contents, but, mainly, our daily practices. Therefore we bring to the center of debate school projects as one of the pedagogical possibilities that apart from its action flexibility also allows us to upgrade the most immediate social discourses, introducing the daily the necessity this closer interaction between the production of school knowledge and its alignment to everyday living. The analysis object, operating in schools, is the Program "By The Radio Waves", which is part of the educommunicativy projects of Municipal Government of S??o Paulo. From the perspective of Freire's pedagogy and an approach communicative-cultural, especially through the concept about the educommunication, we intend to check if, somehow, this project recovers, or no, the promotion of individuals there involved, the creativity, the team work, and the use of Information and Communication Technologies (ICTs). It is intended, therefore,to verify if education by projects, through educommunicativy actions that relate to the analysis object of this research, contributes or collaborates not only to the cooperative adjustment and dialogic which is expected of these actions, but also to other instances, as a better school performance of students, or, yet, the expansion of its operations inside and outside the school.